A comparative study of mechanical properties and life cycle assessment of high-strength concrete containing silica fume and nanosilica as a partial cement replacement. (December 2022) - Fallah-Valukolaee, Saber; Mousavi, Reza; Arjomandi, Arash; Nematzadeh, Mahdi; Kazemi, Mostafa
Abstract: Employing pozzolanic materials like nanosilica and silica fume as replacements for cement to produce high-strength concrete (HSC) has made investigating the mechanical features of the produced HSC and assessing impacts that producing these materials have on the environment a necessity. Therefore, this paper aimed to assess the mechanical properties, environmental impacts and life cycle of HSC containing silica fume and nanosilica where its compressive performance and microstructure were evaluated and a comparison between the effects of pozzolanic materials were compared with those of ordinary cement on environmental indices. Concrete specimens were made using seven mix designs, and different parameters, namely compressive capacity, toughness, strain at peak stress, relative energy absorption, and stress–strain relationship were evaluated. Afterward, some empirical relationships were proposed to capture concrete mechanical features. Here, silica fume at contents of 0, 8, 10, and 12 % and nanosilica at contents of 0, 1, 2, and 3 % were used as a weight replacement of cement. Further, using the atomic force microscopy (AFM) images, the microstructure of the concrete without the pozzolans and concretes with silica fume and nanosilica was studied. In addition, to investigate the environmental impacts of the concretes containing silica fume and nanosilica and conventional concrete, two methods of problem-oriented CML 2000 and damage-oriented IMPACT 2002+ were employed in SimaPro8.1 program. In this procedure, environmental parameters including acidification, eutrophication, global warming potential (GWP), human health, and ecosystem quality, and natural resources were investigated. Finally, for validation, all the obtained results were compared with those obtained using the building for environmental and economic sustainability (BEES) approach. It was found that the best weight percentages of silica fume and nanosilica replacing cement were 12 and 2 %, respectively, which led to improvement in the performance of the HSC under compression. Moreover, the proposed prediction models for the compressive performance of the HSC using empirical formulations developed for the mechanical features correlate well with the test results. Based on the CML 2000 method, the concrete containing 12 % silica fume has the greatest environmental damage in the acidification, human toxicity, and eutrophication categories, for which the corresponding indices were 6.6, 2.4, and 4.3 times those of the reference concrete. Further, by employing the damage assessment method IMPACT 2002+, the HSC with 12 % silica fume was found to have the highest damage in human health, ecosystem quality, and natural resources, for which the corresponding indices were respectively 4.7, 3.5, and 4.6 times those of the reference concrete. All the environmental indices of the HSC without the pozzolans were lower in comparison with the other concretes except for the climate change index which was higher for the HSC without the pozzolans than the other specimens.